Menuju Birokrasi Inklusif: Implementasi Kebijakan Kesetaraan Gender di Sektor Publik - Mayasari, Ayu Dewi; Dama, Melati; Situmorang, Lisbet (Citra Media Publishing, 2025)
This study analyzes how gender equality policies are implemented in the Indonesian bureaucracy. Although policies such as Gender Mainstreaming (PUG) and Gender Responsive Budgeting (ARG) have been implemented, there are still gaps in implementation. The main obstacles to achieving gender equality in the bureaucracy include a patriarchal organizational culture, a lack of policy oversight mechanisms, and limited capacity building programs for women. This study uses a qualitative approach to explore the impact of the gender gap in the bureaucracy. Data was collected using a literature review method on studies that evaluated the implementation of gender equality policies in public administration in Indonesia. This study shows that the effectiveness of gender equality policies is strongly influenced by three main factors: organizational culture, policy supervision, and strengthening the capacity of women in the bureaucracy. An organizational culture that still maintains patriarchal norms creates barriers for women to gain equal access to promotions. Weak policy oversight leads to a lack of accountability in the implementation of gender equality policies. Meanwhile, strategies to strengthen women's capacity, such as mentorship and leadership training, are still not fully institutionalized in the bureaucratic system. Therefore, gender equality-oriented bureaucratic reform must include improvements in these three aspects to create more substantial changes.